Sustainable Airport Development In Indonesia's Border Areas: Challenges and Future Prospects Case Study of Letung Airport, Regency Anambas Islands Riau Islands Province - Hendra Suryaka, Andy; Utami Ady, Sri (Asian Journal of Social and Humanities, 2024)
The construction of airports in Indonesia's border areas has a strategic role in supporting connectivity and economic development in border areas. This study uses survey methods and interviews from several respondents in the district of Anambas Islands, Riau Islands Province. Several findings related to the challenges and prospects of airport development in the border area have a positive impact on the community on the border, especially in the Riau Islands Where this area is almost 96% consisting of interview data which shows that 90% feel the benefits and 10% provide input for the next development, making the essence of the airport in the border area very much needed. However, the question is still how sustainable the airport development is. Whether it is completed with the operation of an airport or is it still being developed to continue to provide benefits to the community as the main target.